2021
DOI: 10.3390/children8100837
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Dimethylarginine (ADMA) in Pediatric Renal Diseases: From Pathophysiological Phenomenon to Clinical Biomarker and Beyond

Abstract: Asymmetric dimethylarginine (ADMA), an endogenous nitric oxide (NO) synthase inhibitor, inhibits NO synthesis and contributes to the pathogenesis of many human diseases. In adults, ADMA has been identified as a biomarker for chronic kidney disease (CKD) progression and cardiovascular risk. However, little attention is given to translating the adult experience into the pediatric clinical setting. In the current review, we summarize circulating and urinary ADMA reported thus far in clinical studies relating to k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 83 publications
(132 reference statements)
0
9
0
Order By: Relevance
“…According to Shafi et al, ADMA and SDMA are pseudo-uremic toxins that can induce toxicity through a number of mechanisms, including disturbances in the synthesis of nitric oxide and the formation of reactive oxygen species [ 33 ]. Plasma ADMA levels do not correlate with blood creatinine or eGFR levels in children and adolescents with CKD, most likely because most ADMA is enzymatically degraded, in the opinion of Hsu Chien-Ning et al [ 34 ]. While our observations showed a statistically negative correlation between ADMA and GFR in children with CKD ( Figure 4 ), as also reported by Benito [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Shafi et al, ADMA and SDMA are pseudo-uremic toxins that can induce toxicity through a number of mechanisms, including disturbances in the synthesis of nitric oxide and the formation of reactive oxygen species [ 33 ]. Plasma ADMA levels do not correlate with blood creatinine or eGFR levels in children and adolescents with CKD, most likely because most ADMA is enzymatically degraded, in the opinion of Hsu Chien-Ning et al [ 34 ]. While our observations showed a statistically negative correlation between ADMA and GFR in children with CKD ( Figure 4 ), as also reported by Benito [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Competitive inhibitor of eNOS such as ADMA lowers NO synthesis ( Hsu and Tain, 2021 ). Decreased NO also gives rise to unabated ET-1 actions that contribute to vasoconstriction, thereby increasing blood pressure ( Böger and Ron, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…In CKD, renal L-citrulline uptake is reduced, the amount of L-citrulline converted to L-arginine in the kidney is diminished, and plasma L-citrulline levels and turnover are increased [ 74 ]. In children with CKD stages 1–3, a high plasma ratio of L-citrulline-to-L-arginine significantly correlated with abnormal ABPM profile, including nocturnal hypertension, increased diastolic BP load, and nocturnal BP non-dipping [ 75 ]. Another study indicated that the plasma ratio of L-arginine-to-ADMA, an index of NO bioavailability [ 76 ], was elevated in children with CKD stages 2–3 and positively correlated with BP.…”
Section: Cardiovascular Risks and Biomarkers In Pediatric Ckdmentioning
confidence: 99%
“…Several studies found plasma ADMA levels were elevated in children with pre-dialysis CKD [ 78 , 79 , 80 ]. Additionally, elevated plasma ADMA levels occur in parallel with increased BP loads [ 75 ] and AI [ 77 ].…”
Section: Cardiovascular Risks and Biomarkers In Pediatric Ckdmentioning
confidence: 99%